2008
DOI: 10.1111/j.1365-2109.2008.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

The amount of calcium in bony structures used for age determination in Cyprinion macrostomus (Heckel, 1843)

Abstract: In this study, the ages of 76 individuals belonging to the Cyprinion macrostomus (Heckel, 1843) population caught from Murat River near Bing˛l city were determined from six di¡erent bony structures and the level of calcium mineral of each bony structure was measured using an atomic absorption spectrophotometer. The determined element was statistically examined according to the age, length, weight and sex of the ¢sh. The age, length and weight ranges of the ¢sh were found to be 2^6, 12.0^21.2 mm and 16.3^135.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Chi-square analysis showed that there was no significant difference from the expected ratio of 1:1. The sex ratio of C. macrostomus was 0.75:1 in the Dalaki River (Sedaghat and Hoseini, 2012), and it was 0.80:1 in the Murat River (Aydın et al, 2008) (Table 2). The sex ratio of the fish populations changed based on spawning season, life stage of the fish, spawning ground, and migration (Nikolsky, 1963;Bartulovic et al, 2004).…”
Section: Gsi = (Wg / W) × 100mentioning
confidence: 99%
See 1 more Smart Citation
“…Chi-square analysis showed that there was no significant difference from the expected ratio of 1:1. The sex ratio of C. macrostomus was 0.75:1 in the Dalaki River (Sedaghat and Hoseini, 2012), and it was 0.80:1 in the Murat River (Aydın et al, 2008) (Table 2). The sex ratio of the fish populations changed based on spawning season, life stage of the fish, spawning ground, and migration (Nikolsky, 1963;Bartulovic et al, 2004).…”
Section: Gsi = (Wg / W) × 100mentioning
confidence: 99%
“…The oldest specimens of C. macrostomus reported were 6 years old in the Murat River (Aydın et al, 2008) ( Table 2). In this study, age distributions were between age groups 0 and IV, and the majority of specimens belonged to age group I for both species, which proved that the fish populations were young.…”
Section: Gsi = (Wg / W) × 100mentioning
confidence: 99%
“…Ca 2+ supports muscle contraction, blood vessel expansion and contraction, secretion of hormones and enzymes, and transmission of impulses throughout the nervous system. 3 Furthermore, Ca 2+ has been implicated in preventing colon cancer and osteoporosis. 4 An increasing number of people in aging societies are at risk of deciency of calcium, which must be supplied by their diets.…”
Section: Introductionmentioning
confidence: 99%